2007
DOI: 10.1007/s00265-007-0381-7
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and costs of earwig (Forficula auricularia) family life

Abstract: The evolution of parental care and family group formation critically depends on offspring survival benefits and parental fecundity costs of care under given ecological conditions. Investigations of the functional significance of care in insect species that exhibit facultative parental care have been relatively rare but may be of particular interest for better understanding of benefit and cost schedules at an early evolutionary stage. In this study, aspects of benefits and costs of care were addressed in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
200
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(209 citation statements)
references
References 42 publications
4
200
0
1
Order By: Relevance
“…[4,28]). Previous studies already revealed that the maternal presence reduces nymph survival when families had restricted food access [21], but increased nymph survival when families had access to low quality food [15]. Here, the effects of maternal presence under ad libitum, high quality food could reveal an increased expression of sibling rivalry when juveniles have access to maternal resources, as proposed in a recent model [29].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…[4,28]). Previous studies already revealed that the maternal presence reduces nymph survival when families had restricted food access [21], but increased nymph survival when families had access to low quality food [15]. Here, the effects of maternal presence under ad libitum, high quality food could reveal an increased expression of sibling rivalry when juveniles have access to maternal resources, as proposed in a recent model [29].…”
Section: Discussionmentioning
confidence: 51%
“…However, investigating the occurrence of these effects in precocial invertebrates, in which juveniles exhibit early foraging capabilities and consequently only facultatively rely on parental resources [14,15], could provide crucial information on the early evolution of parental care. Indeed, transgenerational costs could be a key promoter of the maintenance of family life when parental loss has limited (if any) short-term costs in terms of offspring survival, a scenario that applies to precocial systems and probably prevailed in the early evolution of family life [16].…”
Section: Introductionmentioning
confidence: 99%
“…But such parental care often comes at costs to parents (see [1,2] for a review). For instance, it may reduce their capability to invest in future reproduction, delay successive broods or decrease their likelihood to survive until the next reproductive period [3,4]. To maximize fitness returns on investment, parents are expected to adjust their level of care in relation to variation in benefits to offspring and in costs to themselves [5].…”
mentioning
confidence: 99%
“…In line with this idea, positive associations between resource availability and parental care have been reported in a few altricial species where offspring cannot survive without care (reviewed in [1]). While such patterns provide information about when parents should stop caring owing to enhanced costs, these studies are of limited relevance to understand how environmental quality shapes the early evolution of parental care and family life [4,11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation